2016
DOI: 10.1371/journal.pone.0159132
|View full text |Cite
|
Sign up to set email alerts
|

HMGB1/RAGE Signaling and Pro-Inflammatory Cytokine Responses in Non-HIV Adults with Active Pulmonary Tuberculosis

Abstract: BackgroundWe aimed to study the pathogenic roles of High-Mobility Group Box 1 (HMGB1) / Receptor-for-Advanced-Glycation-End-products (RAGE) signaling and pro-inflammatory cytokines in patients with active pulmonary tuberculosis (PTB).MethodsA prospective study was conducted among non-HIV adults newly-diagnosed with active PTB at two acute-care hospitals (n = 80); age-and-sex matched asymptomatic individuals (tested for latent TB) were used for comparison (n = 45). Plasma concentrations of 8 cytokines/chemokine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 50 publications
(125 reference statements)
0
22
0
Order By: Relevance
“…S100A12 has a dual role inducing both proinflammatory and antimicrobial effects by interacting with different receptors, such as RAGE and TLR4 (28). RAGE expression is associated with disease severity and levels of proinflammatory cytokines in active tuberculosis (TB) (29). Contrary, RAGE is protective against the development of pulmonary TB in mouse models (30) in line with reduction of antimicrobial activity in human macrophages upon TLR2/1 ligand activation by S100A12 knockdown (20).…”
Section: Discussionmentioning
confidence: 99%
“…S100A12 has a dual role inducing both proinflammatory and antimicrobial effects by interacting with different receptors, such as RAGE and TLR4 (28). RAGE expression is associated with disease severity and levels of proinflammatory cytokines in active tuberculosis (TB) (29). Contrary, RAGE is protective against the development of pulmonary TB in mouse models (30) in line with reduction of antimicrobial activity in human macrophages upon TLR2/1 ligand activation by S100A12 knockdown (20).…”
Section: Discussionmentioning
confidence: 99%
“…TB is a chronic infectious disease with a spectrum of symptoms and presentations, wherein cytokines and chemokines play important roles in manipulation of the immune responses, containment of Mtb , pathogenesis and disease manifestations. Various studies have compared serum cytokine/chemokine profiles of patients with different clinical presentations of TB, to establish the expression levels as early surrogate biomarkers of therapeutic responses, bacteriological confirmation of TB and sputum culture conversion [ 31 33 ]. We measured cytokines and chemokines in culture supernatants of PBMC instead of serum or plasma, and the findings were similar to previous studies, showing marked decline of serum cytokine/chemokine concentrations at different treatment stages [ 14 , 33 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have compared serum cytokine/chemokine profiles of patients with different clinical presentations of TB, to establish the expression levels as early surrogate biomarkers of therapeutic responses, bacteriological confirmation of TB and sputum culture conversion [ 31 33 ]. We measured cytokines and chemokines in culture supernatants of PBMC instead of serum or plasma, and the findings were similar to previous studies, showing marked decline of serum cytokine/chemokine concentrations at different treatment stages [ 14 , 33 37 ]. Particularly we found that compared to conventional anti-TB treatment in the placebo group, cytokine/chemokine reduction was greater in the PBA or vitD 3 groups that occurred in parallel to clinical recovery [ 25 ] (reduced TB score), suggesting a role of PBA and vitD 3 in dampening of inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another possible approach for further research on endosomal RNA-sensing of MTB could be the receptor for advanced glycation end products (RAGE), which has been found to enhance, among others, endosomal RNA transport of extracellular RNA [44]. Human DCs and monocytes during active TB exhibited an increase in RAGE expression on cell membranes [45], and among a Brazilian TB cohort, levels of soluble RAGE were higher than in healthy controls [46].…”
Section: Tlr3-recognizing Dsrnamentioning
confidence: 99%